2018
DOI: 10.14744/anatoljcardiol.2017.7957
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the longitudinal deformation of the left ventricular myocardium in subjects with impaired fasting glucose with and without increased glycated hemoglobin

Abstract: ObjectivePrediabetes comprises a heterogeneous group because of the poor concordance of its definition. The aim of our study was to evaluate the longitudinal deformation of the left ventricular (LV) myocardium at the two opposite ends of the prediabetes spectrum as defined by fasting blood sugar and glycated hemoglobin (HbA1c).MethodsEighty consecutive subjects in a cross-sectional single-center study with impaired fasting glucose (IFG) (100–126 mg/dL) and without significant epicardial coronary artery stenosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Our investigation reported that LV mass index, LA longitudinal strain, and three-dimensional LV area strain were independently associated with HbA1c in the study population that involved prediabetic and diabetic patients ( 5 ). Akavan-Khaleghi et al ( 6 ) did not find an independent association between LV GLS and HbA1c. However, the authors did not consider simple correlation analysis between HbA1c and LV GLS.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Our investigation reported that LV mass index, LA longitudinal strain, and three-dimensional LV area strain were independently associated with HbA1c in the study population that involved prediabetic and diabetic patients ( 5 ). Akavan-Khaleghi et al ( 6 ) did not find an independent association between LV GLS and HbA1c. However, the authors did not consider simple correlation analysis between HbA1c and LV GLS.…”
mentioning
confidence: 88%
“…Interestingly, LV GLS significantly dropped when controls were compared with participants with isolated increased fasting glucose, whereas there was no significant difference between individuals with various levels of glucose intolerance ( 3 ). In other words, the most important feature that induced LV remodeling was the existence of insulin resistance but not its severity, which could partly explain the results of the study by Akavan-Khaleghi et al ( 6 ).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…IFG and normal HbA1c. 3 Estimates of the prevalence of left ventricular diastolic dysfunction (LVDD) in T2DM range from 23% to 54%. 4 Moreover, diabetes duration longer than four years was independently associated with LVDD -left ventricular diastolic filling pressure (E/e´ ratio) greater than 15 (normal value <8) -even after adjustment for age, gender, body mass index (BMI), prior CAD, prior systemic hypertension and LVEF.…”
Section: Effects Of Physical Exercise On Left Ventricular Function In...mentioning
confidence: 99%
“…The accompanying fiber which is metabolized as a part of a complete food naturally decelerates and modulates fructose release [6]. The overconsumption of either natural or refined fructose increases in recent years and this increase is believed to have a relation with some diseases such as insulin resistance, type-2 diabetes, hyperglycemia, cardiovascular diseases and especially obesity [7][8][9].…”
Section: Introductionmentioning
confidence: 99%